Bifunctional ternary manganese oxide/vanadium oxide/reduced graphene oxide as electrochromic asymmetric supercapacitor - Mohanadas, Dharshini; Azman, Nur Hawa Nabilah; Abdullah, Jaafar; Endot, Nor Azam; Sulaiman, Yusran (Elsevier, 2021)
A bifunctional ternary manganese oxide/vanadium oxide/reduced graphene oxide (MnO2/V2O5/rGO) was developed for asymmetric electrochromic supercapacitor (EC-SC) application. The elemental mapping revealed uniformly distributed MnO2, V2O5 and rGO, depicting homogenous synthesis of the hybrid composite. The phase composition, vibration modes and valance state of the ternary composite were analyzed via X-ray diffraction (XRD), Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) analysis, respectively. Interestingly, the as-prepared MnO2/V2O5/rGO composite disclosed tremendous Csp of 1403.5 F/g, which was higher compared to MnO2/V2O5 (801.1 F/g), V2O5 (613.1 F/g), MnO2 (126.7 F/g) and rGO (60.7 F/g). MnO2/V2O5/rGO that appeared in dark green switched its visual color to orange at the charged state, confirming the electrochromic property. The bifunctional manganese oxide/vanadium oxide/reduced graphene oxide//copper-based metal-organic framework/reduced graphene oxide (MnO2/V2O5/rGO//MrGO) asymmetrical EC-SC device revealed outstanding cycling stability (90.3% charge retention over 5000 cycles), tremendous specific capacitance (652.7 F/g) and maximum specific energy (60.4 Wh/kg). MnO2/V2O5/rGO//MrGO asymmetrical EC-SC device demonstrated reversible color changes from dark green to orange at the discharged and charged states, respectively. The significantly great electrochromic and supercapacitive performance revealed that MnO2/V2O5/rGO//MrGO is an outstanding electroactive candidate for the next generation of electrochromic supercapacitors.